Metabolic Recycling Enhances Proliferation in MYC‐Transformed Lymphoma B Cells (Adv. Biology 2/2023). Issue 2 (17th February 2023) - Zhang, Cissy; Hoang, Giang; Attarwala, Nabeel; Cooper, Arthur J. L.; Asaka, Ryoichi; Le, Anne
Abstract : Metabolic Recycling In article number 2200233, Anne Le and co‐workers study cancer relapse after treatment and the phenomenon of metabolic recycling, which may help to partially explain why cancer relapse occurs. Specifically, they find that surviving live cancer cells are able to take up the metabolites from the post‐therapy environment containing debris of the dead cancer cells and incorporate these metabolites into their metabolism, thus promoting proliferation.